Developing a Personal and Social Identity With Type 1 Diabetes During Adolescence: A Hypothesis Generative Study. (April 2016) - Commissariat, Persis V.; Kenowitz, Joslyn R.; Trast, Jeniece; Heptulla, Rubina A.; Gonzalez, Jeffrey S.
This study explored the incorporation of type 1 diabetes mellitus (T1DM) into self-identity among adolescents. Guided interviews explored 40 adolescents' views of T1DM in relation to their sense of self and relationships with others. Responses were analyzed using thematic analysis. Results revealed that the entire sample described T1DM as a significant burden; many described how T1DM made them feel less "normal." Adolescents described both positive and negative aspects of self-management in social relationships, though most reported benefits in sharing T1DM with friends. Females were more likely to share information about T1DM and to describe positive changes in self-perception as a result of T1DM. The psychosocial processes related to integration of T1DM into self-identity described in these qualitative data provide hypothesis-generating findings that can guide future quantitative research examining incorporation of T1DM into adolescent self-identity in relation to measures of self-esteem, peer orientation, self-management, and glycemic control.